Rhetorical Move Analysis on the University Students' Presentation: Move in the Oral and PowerPoint Slide Presentation - Khairatun Nisak; Slamet Setiawan (Institut Agama Islam Negeri Madura, 2023)
There is a limited study view on rhetorical moves employed in both students’ oral presentations and PowerPoint slides in the classroom presentation. Few studies are largely realized on oral and slide movement in the conference and thesis presentation. Furthermore, the purpose of this research paper is to expose what are move employed by students in presenting classroom course project presentation orally and on slide, and what moves which is hampered in both. A qualitative survey based on the observation technique was used for data collection purposes. Data are analyzed using two divergent theoretical frameworks. The finding reveals students employ four moves of oral presentation; introduction, body, conclusion, and Q&A move. Otherwise, the Powerpoint slide highlights two moves including the body and conclusion move, the opening move seems optional. Further, orally, the omission of a summarization step in the conclusion move hampers students in reminded any point of the presentation thereby hampers the audience in strengthening their recall and understanding. The transition between spoken and written genres within the PowerPoint slide hampers through the dissipation move in both. Thus, the teacher should take into account the importance of rhetorical knowledge toward the presentation movement either in the oral or PowerPoint slides.